Comprehensive analysis on 559 cases of adrenal incidentalomas in the elderly Chinese. Issue 1 (24th March 2018) - Li, Tuo; Li, Weiqin; Fang, Xiao; Lv, Qian; Song, Yan; Shi, Yongquan
Abstract: Objective: This study was conducted to describe the incidence, classifications and characteristics of adrenal incidentalomas (AIs) in the elderly Chinese. Methods: Primary clinical records in Shanghai Changzheng Hospital (n = 559) were collected for incident cases of AI between January 1, 2002 and December 1, 2016. We examined demographics, endocrine functions, treatment, etiology, and prognoses. Results: We identified 559 new diagnoses of elderly onset AIs, of which 41.25% were male and were diagnosed at a mean age of 74.39 ± 9.03 years. About 61% showed no typical symptoms. Upon systematic review, 41.34% showed dysglycemia, high blood pressure, kaliopenia, and so on. 24.15% (n = 135) received complete or partial endocrine function assessments. A total of 281 cases underwent surgical treatment, and 278 cases went through regular follow‐ups without any operation. Preoperative evaluation was basically consistent with postoperative pathology (P > .05). During the follow‐up, the presence of new subclinical hypercortisolism was 8.99%, and the tumor grew up 3.92% per year (1.96 ± 0.09 mm). 51 cases (9.12%) eventually received further invasive examinations or surgical treatments. Conclusion: The detection of AI in the elderly Chinese is increasing annually. The imaging method and endocrine function tests have great roles in distinguishing between benignancy and malignancy. The diagnosis and treatment of the elderly Chinese with AI should receive multidisciplinary assessment. Biochemical and morphological follow‐up of aged patients with AI should be conducted every 5 years at least.